Beyond bureaucracy: Rethinking educational governance through school-based management in Indonesia - Hendri Hendri; Rudi Hartono; Jatmiko Budi Santoso; Robi Hendra; Indria Nurfadanti; Hansein Arif Wijaya (Jurnal Sinar Edukasi, 2025)
This analysis examines the contemporary state and future trajectory of school-based management (SBM) in Indonesian basic education, evaluating its implementation two decades after national decentralization reforms. Drawing on policy documents, empirical studies, and institutional data, this paper analyzes how SBM has transformed governance structures in elementary and junior secondary schools across Indonesia's diverse educational landscape. The analysis reveals a complex implementation pattern characterized by significant regional disparities: urban schools demonstrate greater capacity in exercising managerial autonomy, while rural and remote schools struggle with limited resources and inadequate leadership training. Current situations indicate that while legislative frameworks grant schools substantial authority over budgeting, personnel, and instructional decisions, practical implementation is constrained by several factors including ambiguous delegation of authority, insufficient school committee functionality, persistent bureaucratic oversight, and weak accountability mechanisms. However, promising developments emerge in schools that have successfully integrated local cultural content, established productive community partnerships, and utilized participatory planning processes. Prospects for strengthening SBM depend on addressing fundamental capacity gaps through comprehensive professional development for principals, establishing transparent performance indicators, empowering school committees. This analysis concludes that realizing SBM's transformative potential requires systemic reforms that align policy intentions with implementation realities, strengthen grassroots capabilities, and balance school autonomy with national quality assurance in Indonesia's heterogeneous educational context.